2000
DOI: 10.1002/(sici)1097-4679(200001)56:1<149::aid-jclp14>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Boredom proneness: Its relationship to psychological- and physical-health symptoms

Abstract: The relationship between boredom proneness and health-symptom reporting was examined. Undergraduate students (N ϭ 200) completed the Boredom Proneness Scale and the Hopkins Symptom Checklist. A multiple analysis of covariance indicated that individuals with high boredomproneness total scores reported significantly higher ratings on all five subscales of the Hopkins Symptom Checklist (Obsessive-Compulsive, Somatization, Anxiety, Interpersonal Sensitivity, and Depression). The results suggest that boredom pronen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 47 publications
7
119
0
14
Order By: Relevance
“…It was recently suggested that the cumulative effects of boredom may be associated with cardiovascular disease and early death (Britton & Shipley, 2010). Undoubtedly, there are other variables that may have contributed to this finding, including associations between boredom proneness and potentially harmful characteristics such as sensation-seeking, impulsivity, and addiction (Sommers & Vodanovich, 2000). Or, perhaps because activity is less appealing to those who are prone to experiencing boredom, they are more likely to lead a sedentary lifestyle, resulting in increased incidence of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently suggested that the cumulative effects of boredom may be associated with cardiovascular disease and early death (Britton & Shipley, 2010). Undoubtedly, there are other variables that may have contributed to this finding, including associations between boredom proneness and potentially harmful characteristics such as sensation-seeking, impulsivity, and addiction (Sommers & Vodanovich, 2000). Or, perhaps because activity is less appealing to those who are prone to experiencing boredom, they are more likely to lead a sedentary lifestyle, resulting in increased incidence of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sample items included "In situations where I have to wait, such as a line or queue, I get very restless" (situation) and "I find it easy to entertain myself" (personal characteristic). Responses on each item were summed to obtain a total score ranging from 28-196, with higher scores reflecting greater proneness to experiencing boredom (Sommers & Vodanovich, 2000;Vodanovich et al, 1991;Watt & Vodanovich, 1999). The original true/false version of the scale demonstrates adequate internal consistency (α = .79), and test-retest reliability over a duration of one week (r = .83; Farmer & Sundberg, 1986).…”
Section: Study 1 -Validation Of Video Clipsmentioning
confidence: 99%
“…trait boredom) dotyczy uczniów, u których występuje znacznie większe niż w przypadku grupy (A) prawdopodobieństwo ulegania negatywnym emocjom, co często pociąga za sobą wybuchy złości i agresji oraz trudności w zapanowaniu nad nimi. Ten typ nudy najczęściej dotyczy impulsywnie zachowujących się jednostek ekstrawertycznych i jest kojarzony z niskim poziomem osiągnięć, tendencją do opuszczania zajęć, uzależnieniami i zaburzeniami nawyków żywieniowych (Sommers i Vodanovich, 2000).…”
Section: Typologie Nudyunclassified
“…The data were insufficient, however, for developing a causal model of the relation between attention lapses and affective dysfunction as reflected in boredom. Nonetheless, we proposed the hypothesis that a potential consequence of a chronic inability to engage and sustain attention is a lack of interest in everyday events, as is typically experienced in boredom, leading to a loss of meaning in everyday tasks, a lack of motivation, and persistent negative affect (O'Hanlon, 1981;Sommers & Vodanovich, 2000).…”
Section: Introductionmentioning
confidence: 99%